NEW CONCEPTIONS OF INTERNATIONAL CRIMES AGAINST HUMANITY AND POSSIBLE JURISDICTION OF THE INTERNATIONAL CRIMINAL COURT ON ENVIRONMENTAL CRIMES (CIPEEX, 2022)
THE ARTICLE AIMS TO DEVELOP AN ANALYSIS ON THE INTERNATIONAL CRIMINAL COURT JURISDICTION TOACT ON ENVIRONMENTAL CRIMES AND CRIMES AGAINST HUMANITY. CONSIDERING THE OBSERVANCE ANDPREVALENCE OF FUNDAMENTAL RIGHTS, AS WELL AS THE PRINCIPLE OF SOVEREIGNTY, CONSTITUTIONALFOUNDATION OF THE BRAZILIAN STATE. THE DISCUSSION ON THE SUBJECT AIMS TO ANALYZE, DEFINE ANDCHARACTERIZE ENVIRONMENTAL RESPONSIBILITY, AS WELL AS ESTABLISH MEASURES THAT EXPANDINTERNATIONAL JURISDICTION TO ACT IN ENVIRONMENTAL CRIMES. REGARDING METHODOLOGY, THE INITIALPROPOSAL CONSISTS OF USING THE BIBLIOGRAPHICAL RESEARCH TECHNIQUE IN RELATION TO THE THEME (BOOKS,ARTICLES, THESES AND DISSERTATIONS), AND PERTINENT NATIONAL AND INTERNATIONAL LEGISLATION, WITH THEPURPOSE OF IDENTIFYING THE DIFFERENT INTERPRETATIONS OF THE AUTHORS ON THE SUBJECT. THE RESEARCHAPPROACH IS HYPOTHETICAL-DEDUCTIVE. WE SEEK TO VERIFY THE POSSIBLE ACTION OF THE INTERNATIONALCRIMINAL COURT IN CASES OF ENVIRONMENTAL TRAGEDIES, CONSIDERED AS ECOCIDE IN BRAZIL, AND TOPRESENT CONTRIBUTIONS TO SOLVE THE PROBLEM. WITH THE PURPOSE OF RAISING SPECIFIC DATA ON MAJORTRAGEDIES, UNDERSTANDING THE PROBLEMS CAUSED TO THE POPULATIONS AND TO THE ENVIRONMENT, ANDFINALLY, VERIFYING THE POSSIBLE CONTRIBUTIONS OF INTERNATIONAL ENVIRONMENTAL LAW IN CASES OFECOCIDE IN BRAZIL.
Keywords: direito; competência; ecocídio